Improving understanding of drought using extended and downscaled GRACE data in the Pearl River Basin - Xiangyu Wan; Wei You; Xinchun Yang; Dongming Fan (Journal of Hydrology: Regional Studies, 2025)
Study regions: The Pearl River Basin, China. Study focus: The terrestrial water storage anomalies (TWSA) tracked by the Gravity Recovery and Climate Experiment (GRACE) mission are valid observations for drought monitoring. However, the coarse resolution and short duration limit their potential applications at local scales. In previous studies, these drawbacks are addressed by statistical downscaling and hindcasting techniques, but usually as two separate processes. In this study, a novel deep learning model is designed to integrate downscaling and hindcasting into a unified framework. Based on the TWSA generated by this model, the drought recovery rate, the propagation threshold of hydrological drought, and their dynamics are investigated with longer duration (1982–2017) and finer spatial resolution (0.1 degree). New hydrological insights for the region: The basin is more vulnerable to hydrological drought in the last three decades. Droughts occurred in 16 % of months, with an average duration of 6.3 months and an average recovery time of 4.5 months before 2002, the proportion increased to 33 %, with an average duration of 7.8 months and an average recovery time of 4.7 months after 2002. The propagation threshold for hydrological drought in the basin is loosening, with basin-averaged changes of 0.03 and 0.02 per year for abnormally dry and moderate drought scenarios, respectively. Nevertheless, the central portion exhibits increased resilience to hydrological drought as precipitation increases and temperature falls.